Granulomas in the tongue of reindeer (Rangifer tarandus L) - Rehbinder, Claes; Nordkvist, Magnus (Rangifer, 1983)
In 3 out of 33, 11 months old male reindeer which during around 3 months had been kept on comercial fodder, granulomas were found at autopsy, in the submucosa of the ventrolateral aspect of the tounge. In two of the granulomas were present worms of genus Onchocerca but also colonics of bacteria. The third granuloma comprised of a suppurative small necrotizing ulceration of the mucosa containing vegetable cells and a granuloma in the underlaying submucosa containing filamentous bacteria typical for necrobacillosis. Outbreaks of necrobacillosis, affecting the mouth and digestive organs, in connection with supplementary feeding, appears to be of multifactorial genesis. Abrasions or other injuries of the oral mucosa caused by parasitic granulomas or sharp vegetable matters in the fodder or from troughs may contribute to outbreaks of necrobacillosis.Granulom i tungan på ren (Rangifer tarandus L)Abstract in Swedish / Sammanfattning: På 3 av 33, 11 månaders renar som gått i utfodring i c:a 3 månaders tid, påvisades, vid obduktion, submucosa årtstora granulom ventro-lateralt på tungan. I två av fallen inneholl granulomen maskar av genus Onchocerca men också bakteriehårdar medan i det tredje fallet forelåg en mindre suppurativ necrotiserande ulceration i mucosan innehållande våxtdelar medan i underliggande submucosa fanns ett granulom innehållande bakteriehårdar, med filamentosa bakterier, typiska for necrobacillos. Utbrott av necrobacillos, affecterande munhåla och digestionsorgan, i samband med utfodring av ren torde vara orsakade av ett flertal olika faktorer. Skador i munslemhinnan orsakade av vassa våxtdelar i foder eller från krubbor eller av suppurerande parasitåra granulom torde kunna vara bidragande orsaker till utbrott av necrobacillos.